Gender difference in the association of hyperuricemia with hypertension in a middle-aged Chinese population. (December 2014) - Wang, Su-Fang; Shu, Long; Wang, Shuai; Wang, Xiao-Qin; Mu, Min; Hu, Chun-Qiu; Liu, Kai-Yong; Zhao, Qi-Hong; Hu, An-La; Bo, Qing-Li; Tao, Fang-Biao; Sheng, Jie
Abstract In this study, we report the relationship between hyperuricemia and hypertension in a middle-aged Chinese population, emphasizing the difference of gender. The cross-sectional study was conducted among 1776 adults aged 45–60 years, who participated in the Hefei Nutrition and Health Study (2012). Hyperuricemia was defined as serum uric acid (SUA)> 420 μmol/l for men, and > 360 μmol/l for women. Hypertension was defined as systolic blood pressure (SBP) ≥ 140 mmHg or diastolic blood pressure (DBP) ≥ 90 mmHg. Anthropometric measurements and biochemical data were collected using standardized procedures. Multivariate logistic regression analysis was performed to determine the relationship between hyperuricemia and hypertension with adjustment of potential confounding factors. Body mass index (BMI), waist circumference (WC), SBP, DBP, fasting glucose, SUA and the prevalence of hyperuricemia and hypertension were significantly higher in male than in female (p < 0.001). Females had significantly higher levels of triglycerides (TG) and high-density lipoprotein (HDL)-cholesterol (5.23 ± 0.87 vs 5.12 ± 1.01, p < 0.05, 1.50 ± 0.37 vs 1.28 ± 0.41, respectively.) than males. Simple correlation analysis showed that SUA was positively associated with WC and TG. In addition, after adjusting for potential confounders, hyperuricemia was associated with increased risk of hypertension in both males and females, with odds ratios (95% CI) of 1.680 (1.110–2.543) and 1.065 (1.012–1.118), respectively. Conclusions: The association of hyperuricemia with hypertension was stronger in males than in females, and middle-aged men with hyperuricemia had greater association with hypertension. Our findings remain to be confirmed in future prospective studies.